2021
DOI: 10.3390/ijerph18052601
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experience Related to the COVID-19 Pandemic among Arabic-, Russian- and Somali-Speaking Migrants in Finland

Abstract: Increasing research shows that migrants are disproportionately exposed to coronavirus disease 2019 (COVID-19). However, little is known about their lived experience and related meaning-making. This qualitative study maps COVID-19-related experiences among respondents from three migrant groups living in Finland: Somali-, Arabic- and Russian-speakers (N = 209). The data were collected by telephone interviews over four weeks in March and April 2020. Using inductive thematic analysis, we identified seven themes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
4
20
0
2
Order By: Relevance
“…A recent German study conducted from January to February 2021 also showed higher loneliness scores among individuals with a migration background [ 34 ]. The association with loneliness and perceived social isolation may be explained by the fact that individuals with a migration background may neither be able to travel to family and friends living abroad nor to receive such visits—both due to travel restrictions [ 37 ]. However, previous research already demonstrated that individuals with a migration background reported higher loneliness scores despite having comparable number of social contacts prior to the pandemic (in comparison to individuals without a migration background [ 38 ]).…”
Section: Discussionmentioning
confidence: 99%
“…A recent German study conducted from January to February 2021 also showed higher loneliness scores among individuals with a migration background [ 34 ]. The association with loneliness and perceived social isolation may be explained by the fact that individuals with a migration background may neither be able to travel to family and friends living abroad nor to receive such visits—both due to travel restrictions [ 37 ]. However, previous research already demonstrated that individuals with a migration background reported higher loneliness scores despite having comparable number of social contacts prior to the pandemic (in comparison to individuals without a migration background [ 38 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all patients belong to Italian nationality, whereas it was reported that migrants and other similar groups showed a particular fear of COVID and may represent an interesting cohort to study also in the CV setting [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…They may fear that they cannot visit these friends and relatives in case of emergency due to potential travel restrictions. Such concerns were also described by a recent qualitative study examining different migrant groups living in Finland during the pandemic [25]. Additionally, fear due to insufficient knowledge about the coronavirus (resulting from language barriers) may also explain the comparably high prevalence rates.…”
Section: Previous Research and Possible Explanationsmentioning
confidence: 92%